INJUSTICE REPRESENTATION IN THE POETRY ANTHOLOGY NYANYIAN AKAR RUMPUT BY WIJI THUKUL (An Analysis Study of Critical Literacy) - Fetti Astrini Rishanjani; Zainal Rafli; Zuriyati Zuriyati (Program Studi Pendidikan Bahasa Program Pascasarjana Universitas Negeri Jakarta, 2019)
ABSTRACT The aim of this research is to do an in-depth study of the representation of injustice cointaned in the anthology of poetry Nyanyian Akar Rumput written by Wiji Thukul and its implication in learning Indonesian language. This research is a qualitative research using descriptive analysis method. The research concludes that the analyzed poems represent acts of injustice, such as commutative and recreative injustice. The results of this research showed: (1) Representation of commutative injustice was found in the poem entitled â€œTanahâ€ that revealed the peopleâ€™s demand of justice caused by land expropriation;(2) Representation of recreative injustice was found in the poem entitled â€œBatas Panggungâ€ that revealed the opposition caused by the lack of freedom in voicing their aspirations;(3) The implication of this research can be used by teachers and students as learning materials for literary study. Keywords: representation of injustice, poetry, critical literacy